Structural and electronic properties of the spinel Li4Ti5O12 - Lkhagvajav, Sarantuya; Tsogbadrakh, Namsrai; Enkhbayar, Enkhjargal; Galsan, Sevjidsuren; Altantsog, Pagvajav (Mongolian Journal of Chemistry, 2019)
In this study, the structure and electronic properties of the spinel compound Li4Ti5O12 (LTO) are investigated both theoretical and experimental methods. The experimental studies of structural and electronic properties were performed by X-ray diffraction and UV-visible spectroscopy. The first principles calculations allowed to establish the relationship between the structure and electronic properties. The spinel type structure of LTO is refined by the Rietveld analysis using the X-ray diffraction (XRD). The band gap of LTO was determined to be 3.55 eV using the UV-visible absorption spectra. The Density functional theory (DFT) augmented without and with the Hubbard U correction (GGA and GGA +U+J0) is used to elucidate the electronic structure of LTO. We have performed systematic studies of the first principles calculations based on the GGA and GGA+U for the crystal structure and electronic properties of spinel LTO. We propose that a Hubbard U correction improves the DFT results.